Climate policy under fat-tailed risk: An application of FUND - David Anthoff; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2010)
We apply four alternative decision criteria, two old ones and two new, to the question of the appropriate level of greenhouse gas emission reduction. In all cases, we consider a uniform carbon tax that is applied to all emissions from all sectors and all countries; and that increases over time with the discount rate. For a one per cent pure rate of the time preference and a rate of risk aversion of one, the tax that maximises expected net present welfare equals 120/tC in 2010. However, we also find evidence that the uncertainty about welfare may well have fat tails so that the expectation exists only by virtue of the finite number of runs in our Monte Carlo analysis. This confirms Weitzman's Dismal Theorem. We therefore consider minimax regret as a decision criterion. As regret is defined on the positive real line, we in fact consider large percentiles instead of the ill-defined maximum. Depending on the percentile used, the recommended tax lies between 100 and 170/tC. Regret is a measure of the slope of the welfare function, while we are in fact concerned about the level of welfare. We therefore minimise the tail risk, defined as the expected welfare below a percentile of the probability density function without climate policy. Depending of the percentile used, the recommended tax lies between 20 and 330/tC. We also minimise the fatness of the tails, as measured by the p-value of the test of the hypothesis that recursive mean welfare is stationary in the number of Monte Carlo runs. We cannot reject the null hypothesis of non-stationary at the 5% confidence level, but come closest for an initial tax of 50/tC. All four alternative decision criteria rapidly improve as modest taxes are introduced, but gradually deteriorate if the tax is too high. That implies that the appropriate tax is an interior solution. In stark contrast to some of the interpretations of the Dismal Theorem, we find that fat tails by no means justify arbitrarily large carbon taxes.
Keywords: 330; climate change; integrated assessment; decision making under uncertainty; deep uncertainty; fat-tailed risk; dismal theorem; Klimaveränderung; Treibhausgas; Kohlendioxid; Ökosteuer; Abzinsung; Entscheidung bei Unsicherheit; Theorie